19g-12g+6-5=-6+44

Simple and best practice solution for 19g-12g+6-5=-6+44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19g-12g+6-5=-6+44 equation:


Simplifying
19g + -12g + 6 + -5 = -6 + 44

Reorder the terms:
6 + -5 + 19g + -12g = -6 + 44

Combine like terms: 6 + -5 = 1
1 + 19g + -12g = -6 + 44

Combine like terms: 19g + -12g = 7g
1 + 7g = -6 + 44

Combine like terms: -6 + 44 = 38
1 + 7g = 38

Solving
1 + 7g = 38

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 7g = 38 + -1

Combine like terms: 1 + -1 = 0
0 + 7g = 38 + -1
7g = 38 + -1

Combine like terms: 38 + -1 = 37
7g = 37

Divide each side by '7'.
g = 5.285714286

Simplifying
g = 5.285714286

See similar equations:

| 2=-4-3n-3n | | M(3-14)=-88 | | -25=10(y-4) | | 2x=243 | | v+3-2=7 | | 26x=243 | | Ix-2I= | | 10=-a+3a | | (3w-1)(8+w)=0 | | 7x-27=3x+1 | | 2y=64 | | 0=7t-t^2 | | 20x+15=20x+28 | | -y=16 | | -y=31 | | 3y=-75 | | s=9-2x | | 6x-1+1=-6 | | -9w+36=-7(w-4) | | 3.25x-1.45=323.55 | | 9x-6+3x=42 | | 3x^2+26x+14= | | 3e^5x=74 | | 2.1*d+.7=7 | | z^2-11x-20=0 | | 4x+25=8x-95 | | 8=-n+5n | | 5x^240=0 | | 4e(2x-1)-200=5000 | | -3a+5=b | | -3-5x=x^2 | | 11=b-1-46 |

Equations solver categories